A REVIEW ON BORDETELLA PERTUSSIS AND THEIR VIRULANCE FACTORS, DIAGNOSIS AND TREATMENT (CAHIERS MAGELLANES-NS, 2024)
Bordetella pertussis, the causative agent of whooping cough, is a highly contagious respiratory pathogen unique to humans. Transmission occurs through respiratory droplets when an infected individual coughs or sneezes.B. pertussis, a rod-shaped Gram-negative bacterium, produces various toxins and antigens that paralyze cilia and impair the respiratory epithelium, leading to mucus accumulation & systemic effects. The pathogen rarely appears in blood cultures, & its toxins including pertussis toxin and tracheal cytotoxin play crucial roles in its virulence. Contemporary research focuses on the pathogenic mechanisms and evolutionary history of Bordetella species, emphasizing their significant antigenic diversity and ability to evade immune responses. Despite advances in vaccination and disease management, pertussis persists as a critical public health issue, necessitating ongoing vigilance and research to mitigate its impact globally. The pathophysiology of B. pertussis involves a toxin-mediated illness that primarily affects the respiratory tract, leading to severe coughing fits, whooping, and post-tussive vomiting. Key virulence factors include pertussis toxin (PT), filamentous hemagglutinin (FHA), pertactin (PRN), and fimbriae, which facilitate bacterial adhesion, immune evasion, and local tissue damage. Treatment typically involves antimicrobial agents, with macrolides such as erythromycin, azithromycin, and clarithromycin being the most commonly used. Vaccination remains the most effective strategy for pertussis prevention. The current immunization schedule includes the DTaP vaccine, which provides protection against diphtheria, tetanus, and acellular pertussis. The vaccine is administered in a series of doses starting at two months of age, with subsequent doses at eighteen months and four to six years, along with booster shots as needed.